Taxonomic review of the species of Helina R.-D. (Diptera: Muscidae) from Andean-Patagonian forests - Patitucci, Luciano Damián; Mulieri, Pablo Ricardo; Mariluis, Juan Carlos (Zootaxa, 2016)
Helina Robineau-Desvoidy, 1830 is the second genus of Muscidae in terms of richness. This genus includes several species collected at high altitudes and high latitudes, and is poorly studied in the Neotropical region. Only 12 species of Helina have been recorded in the southern limit of South America in the Andean-Patagonian forests. In the present work, we studied all the species known from the Andean-Patagonian forests, with the exception of H. viola Malloch, 1934, present three new species, H. araucana sp. nov., H. dorada sp. nov., and H. ouina sp. nov., and provide the first description of the females of H. australis Carvalho & Pont, 1993 and H. rufoapicata Malloch, 1934. We also propose four new synonymies: H. nigrimana basilaris (Carvalho & Pont, 1993) and H. nigrimana grisea (Malloch, 1934) as new junior synonyms of H. nigrimana (Macquart, 1851); and H. fulvocalyptrata Malloch, 1934 and H. simplex Malloch, 1934 as new junior synonyms of H. chilensis Malloch, 1934. Finally, we provide a generic diagnosis and a new key for the Helina species of the Andean-Patagonian forests, as well as notes on the biology and distribution maps of each specimen, and discuss a preliminary contruction of groups of species.